Isolation and Molecular Characterization of Lactobacillus Genus from Patients Wear in Fixed Orthodontic Appliance - Anphal Ihsan Jasim (Journal of Global Pharma Technology, 2016)
Background: The fixed appliances might prevent effective oral hygiene and cause high cariogenic challenge. Objective: This study was examining the presence of lactobacillus Spp by traditional culture and PCR methods. Material and Method: A total 74 patients with age range from 15 to 35with mean age (19.67) that enrolled in this study. The samples were collected from patients admitted to orthodontic department in collage of dentistry during the period from November 2017 to March 2018. The result: The result were shown 59 of 74 was positive result, Thirty eight of 59was positive in PCR technique while 21of 59 positive in culture ,The methods of PCR and growth detected this bacteria was only 35.6%positive in culture ,while PCR methods were 64.4%%. Conclusion: the higher level of bacteria detected by PCR than routine culture method confirm that the PCR method is very sensitive, specific and time consume technique for detecting of oral bacteria.Keywords: Orthodontic Appliances, Lactobacillus, Polymerase Chain Reaction, Biofilm formation, Culture.